2018
DOI: 10.3892/ol.2018.8723
|View full text |Cite
|
Sign up to set email alerts
|

Value of automatic DNA image cytometry for diagnosing lung cancer

Abstract: The present study aimed to investigate the diagnostic value of automatic DNA image cytometry (DNA-ICM) for diagnosing lung cancer. A total of three different types of samples from 465 cases were included: Bronchoalveolar lavage fluid (BALF), 386 samples; pleural effusion cases, 70 samples; and fine-needle aspiration procedures, 9 samples. Two methods, liquid-based cytology (LBC) and automatic DNA-ICM, were used to assess the samples, and the pathological results of 120/465 cases were reviewed. The results of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In some lung cancer cases, it was reported that the bronchial washings were positive detected by DNA‐ICM while negative by conventional cytology. 23 We speculate that the advantage of DNA‐ICM in sensitivity offsets the disadvantage of sampling issues in patients with invisible endobronchial tumor, hence there was no significant difference in the positive rate of DNA‐ICM between the visible tumor group and the invisible tumor group.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In some lung cancer cases, it was reported that the bronchial washings were positive detected by DNA‐ICM while negative by conventional cytology. 23 We speculate that the advantage of DNA‐ICM in sensitivity offsets the disadvantage of sampling issues in patients with invisible endobronchial tumor, hence there was no significant difference in the positive rate of DNA‐ICM between the visible tumor group and the invisible tumor group.…”
Section: Discussionmentioning
confidence: 86%
“…Four relevant studies were found. 6 , 23 , 29 , 30 From the literature review, the sensitivity of DNA‐ICM was 69.05%~90%, and the specificity was 80.28%~100% (Table 5 ). To our knowledge, this is the largest research on the application of DNA‐ICM analysis of bronchial washings in lung cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA‐ICM is a promising screening tool for early lung cancer in high‐risk group 27 . Nevertheless, it was still controversial for diagnosis of lung cancer since some studies yielded inconsistent results 28,29 . This study focused on its diagnosis value in PPLs, which has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research evaluated the cost-effectiveness of DNA ploidy analysis for cervical screening compared with Pap cytology and considered that DNA ploidy strategy appeared to be less costly and comparably effective [19]. The technology of DNA ploidy analysis has become well-established for diagnostic use in several tumors such as endometrial cancer and lung cancer [20,21]. Inexpensive and semiautomated features of DNA ploidy measurement made it an ideal alternative for triaging HPV-positive women in China and other developing countries.…”
Section: Womenmentioning
confidence: 99%